2018
DOI: 10.3758/s13428-018-1129-1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring growth in students’ proficiency in MOOCs: Two component dynamic extensions for the Rasch model

Abstract: Massive open online courses (MOOCs) are increasingly popular among students of various ages and at universities around the world. The main aim of a MOOC is growth in students' proficiency. That is why students, professors, and universities are interested in the accurate measurement of growth. Traditional psychometric approaches based on item response theory (IRT) assume that a student's proficiency is constant over time, and therefore are not well suited for measuring growth. In this study we sought to go beyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The principle of brainstorming with a priori acceptance of everyone's opinion allows not only to come to a common denominator, but also to reveal hidden leadership and oratorical potentials, to remove the barriers of communication, to give an impetus to personal growth and development. Obviously, the majority of people do not enjoy conflicts, and moreover, doctors note the devastating consequences of stresses, most of which are caused by conflict (Bandura, 2017;Abbakumov et al, 2018). Is it possible to say that some style of behavior in a conflict situation is the only right one?…”
Section: Resultsmentioning
confidence: 99%
“…The principle of brainstorming with a priori acceptance of everyone's opinion allows not only to come to a common denominator, but also to reveal hidden leadership and oratorical potentials, to remove the barriers of communication, to give an impetus to personal growth and development. Obviously, the majority of people do not enjoy conflicts, and moreover, doctors note the devastating consequences of stresses, most of which are caused by conflict (Bandura, 2017;Abbakumov et al, 2018). Is it possible to say that some style of behavior in a conflict situation is the only right one?…”
Section: Resultsmentioning
confidence: 99%
“…This approach uses a longitudinal generalised mixed modelling framework to model moment-by-moment learning. The modelling approach has been previously used to model learning in, for instance, an online learning environment with statistics exercises (Kadengye, et al, 2015) and in Massive Open Online Courses (MOOCs; Abbakumov et al, 2019). We briefly describe the most relevant parameters of the modelling approach here, a detailed discussion is provided in online Appendix B.…”
Section: Modelling Learning Efficiencymentioning
confidence: 99%
“…To cover this gap, researchers proposed to measure this growth via the estimation of individual effect of the cumulative sum of video lectures a learner watched before a certain assessment task on the correctness of his/her response this task in a MOOC (Abbakumov, Desmet, & Van den Noortgate, 2019). The use of the extension showed that the probability of the correct response grows with every new watched lecture and the growth effect is specific for individual learners -for some learners, the growth may be intensive, while for some learners it may be almost flat through the whole course.…”
Section: Issues On Measuring Proficiency In Moocsmentioning
confidence: 99%